Determinants of Firm Value - Nurdianti, Cici; Utari, Susan Fitri; Della Febri Rinjani (Systematic Literature Review Journal, 2025)
The purpose of this study was to determine the determinants of company value. The progress of globalization in the business world is currently growing rapidly. This can be seen from the rapid increase in data and innovation that encourages businesses to continue to grow. The company continues to strive to develop in accordance with the times that increase company value. The method used in this research is Systematic literature review (SLR). SLR is a research method to collect and evaluate research results related to topics that will become research topics. The data collection techniques used in this research are observation and literature research methods. The theory is obtained through Google scholar, dimensions, sinta kemendikbud, articles, journals, the data used in this study were collected by means of indirect data collection techniques and sourced from intermediary media the research data collection period is articles from 2023 to 2025. Factors that affect firm value, namely Intelectual Capital Disclosure (ICD), financial performance, and Good Corporate Governance (GCG). Overall, to achieve maximum firm value, business organizations should not only focus on the collection of intellectual capital, but also on openness in its disclosure as well as the implementation of strong GCG practices.